Patient satisfaction for telemedicine health services in the era of COVID-19 pandemic: A systematic review - Kaur, Karuna Nidhi; Niazi, Farah; Thakur, Ruchi; Saeed, Shazina; Rana, Shweta; Singh, Harpreet (Frontiers in Public Health, 2022)
Introduction In the year 2019, the whole world witnessed the COVID-19 pandemic. The pandemic has negatively impacted the health care delivery system. This has risen the necessity among health systems across the world to deliver health care services through telemedicine. This systematic review would assess the level of patient satisfaction with telemedicine health services during the time of the COVID-19 pandemic. Methodology The literature search was conducted in June 2022 using “PubMed” “Google Scholar” and “Embase” databases. A total of eight articles were included. ROBVIS Analysis was performed for the assessment of bias. Descriptive statistics were performed using Microsoft Excel. Results All included studies were conducted in seven countries/states/cities: India (n = 2), Philippines (n = 1), Saudi Arabia (n = 1), UAE (n = 1), Los Angeles (n = 1), Iran (n = 1), and New York City (n = 1). Most used telemedicine tools were voice calls, video calls and messaging/email. Maximum patients used video for consultation (5 out of 9 studies) followed by voice call (4 out of 8 studies), messaging/emails (2 out of 8 studies) and other telemedicine Apps (2 out of 8 studies). Overall, the level of satisfaction was found highest amongst studies conducted in developed countries/states/cities such as New York City (94.9%), Los Angeles (82.7%), UAE (81%) and Saudi Arabia (77.9%) in contrast to studies conducted in developing countries which includes Philippines (82%), India (73.9; 51.3%) and Iran (43.4%). Conclusion Most of the participants were found to be satisfied with the quality of telemedicine they were offered. This systematic review will help to improve telemedicine services which will eventually improve the health care delivery system. Systematic review registration https://www.crd.york.ac.uk/prospero/#myprospero.